PENGARUH BUDAYA ORGANISASI DAN KOMITMEN KERJA TERHADAP KINERJA PEGAWAI LEMBAGA PENYIARAN PUBLIK PADA RADIO REPUBLIK INDONESIA (RRI) SURAKARTA - Amalia, Aufina; Slamet, Giarti (Surakarta Management Journal, 2024)
This research aims to determine the influence of organizational culture and work commitment on the performance of employees of the Public Broadcasting Institution (LPP) Radio Republik Indonesia (RRI) Surakarta located at Jl. Abdul Rahman Saleh No. 51, Kestalan, Banjarsari, Surakarta City, Central Java 57133. This research is a quantitative case study. Primary data was obtained from direct research by distributing questionnaires which were measured using the Linkert scale. The sampling method in this research used nonprobability sampling. The research population was 102 respondents taken from the entire sample. The data analysis method used in this research is multiple linear regression. Hypothesis testing uses the t test and F test. The results of the research show that together the variables of organizational culture and work commitment have a significant effect on employee performance. The influence of organizational culture and work commitment variables is 70.9% on the performance of LPP RRI employees.